Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper analyzes the impact of the adoption of inflation targeting (IT) on exchange rate volatility in Russian Federation. Russia has seen an increase in exchange rate volatility during the past few years compared with the period before the global financial crisis, as the authorities have chosen to allow a higher degree of ruble exchange rate flexibility in preparation for the adoption of IT. The average of the 12-month coefficient of variation of the ruble/dollar exchange rate has also increased from 2.2 percent in December 2005-September 2008 to about 3.7 percent in March 2010-June 2013.